A study of the relations between wage and employment in specific asian countries. - Ng, Thian Choon. (2008)
This study aims to determine whether industrial relations in Hong Kong and Singapore are 'wage-driven' or 'employment-driven'. This is in turn dependent on government policies and the goals of both labour unions and employers in these two countries. Subsequently, empirical results from this research shows that both Hong Kong and Singapore have employment-driven industrial relations regimes while Indonesia, Malaysia, Taiwan and Thailand have the wage-driven ones.